2017
DOI: 10.4103/2041-9414.198906
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Biological Dosimetry at Low and High Doses of Radiation and Radioiodine Impact on Individual Susceptibility to Ionizing Radiation

Abstract: Iodine-131 (I-131) is often used in thyroid diagnostics and therapy. External and internal exposure to radioiodine can lead to molecular and cellular damage in peripheral blood lymphocytes. The aim of this study was to explore the influence of low and high doses of I-131 on susceptibility to ionizing radiation. Study groups consisted of 30 individuals free of thyroid diseases, 41 patients exposed diagnostically to low doses of I-131, and 37 hyperthyroidism patients exposed therapeutically to high doses. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…25,26 Large doses of radiotherapy may kill tumor cells but could also lead to mutation of tumor cells and further differentiation. 27 Molecular subgrouping has already been applied to clinical trials involving a variety of adjuvant therapy schemes, and this classic scheme is likely to be modified or supplanted by a scheme based on molecular subgroups. 28 MB is a highly malignant brain tumor with a poor prognosis in children.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Large doses of radiotherapy may kill tumor cells but could also lead to mutation of tumor cells and further differentiation. 27 Molecular subgrouping has already been applied to clinical trials involving a variety of adjuvant therapy schemes, and this classic scheme is likely to be modified or supplanted by a scheme based on molecular subgroups. 28 MB is a highly malignant brain tumor with a poor prognosis in children.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation for the low gH2AX foci values in samples from 40 Gy BB-irradiated mice with the high dose * area product is the quicker (i.e., complete by 24 hours) repair of DNA damage that was directly inflicted by low doses of scatter radiation. It is also possible that the scatter dose induced an adaptive response (42,43), ameliorating the bystander/abscopal response, although we are not aware of a precedent for such an effect. To add to the complexity of systemic responses in vivo, it should be noted that in directly irradiated cell populations, the relative contribution of bystander damage, compared with directly induced damage sustained by targeted cells, increases with decreasing dose (44,45).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported that chromosome instability varies according to the amount and the repeat number of radioactive iodine taken. Also, it was shown in studies that genetic predisposition, occupational hazard, and life style of individuals exposed to IR can also affect the damage to the cell (26,27). Seo et al (28) showed that incidence of leukemia increases with ≥100 mCi IR.…”
Section: Discussionmentioning
confidence: 99%